Determinants of Audit Fee in Chinese Market - Bai, Luye (2013)
This paper shows the determinants of audit fee in audit market of China. People can see a clearly relationship between determinants like auditor size, auditee size, complexity of auditee, profitability of auditee and audit risk and audit fee in Chinese market. Auditee could know how to make an easy work to auditor so that to reduce the fee for audit. Auditor may have a clearly relationship with auditee. They can keep independence into the processing of audit.